1997
DOI: 10.1159/000276934
|View full text |Cite
|
Sign up to set email alerts
|

Glomangioma of the Nasal Cavity

Abstract: A case of glomangioma of the nasal cavity and the literature concerning this rare tumor are reported. Differential diagnosis, symptoms, pathogenesis and therapy are discussed. This uncommon benign neoplasm is seldom located in the upper respiratory tract. It originates from proliferating arteriovenous capillary anastomoses. Intranasal glomus tumors produce nasal obstruction, epistaxis and sharp pain. The treatment of choice is complete excision of the tumor. The prognosis is excellent when the glomangioma is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The most important feature of treatment is resection of the tumor, as relapse always occurs when surgery is incomplete. According to Arens et al 14 , the rate of recurrence of this benign tumor is 10%.…”
Section: Discussionmentioning
confidence: 97%
“…The most important feature of treatment is resection of the tumor, as relapse always occurs when surgery is incomplete. According to Arens et al 14 , the rate of recurrence of this benign tumor is 10%.…”
Section: Discussionmentioning
confidence: 97%
“…Although glomangiomas are benign, their rate of local recurrence is about 10% [12]. Recurrence is caused by incomplete excision and can be interpreted as residual tumors in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry revealed that the tumor cells stained for muscle actin. [7] 1979 M/24 septum obstruction Potter et al [8] 1984 F/81 septum asymptomatic Morais [9] 1986 M/66 nasal vestibulum asymptomatic Alarcos [10] 1992 M/55 ethmoid sinus obstruction Hayes et al [11] 1993 F/32 nasal vestibulum obstruction Arens et al [12] 1993 M/40 inferior turbinate epistaxis Shimono et al [13] 1998 M/55 ethmoid sinus obstruction Present case 1999 M/42 sphenoid sinus obstruction…”
Section: Case Reportmentioning
confidence: 99%